Influence of different Agrobacterium rhizogenes strains on hairy roots induction and secondary metabolites production in Datura innoxia Mill. - Parisa Naderian; Nasrin Moshtaghi; Abdolreza Bagheri; Saeid Malekzadeh-Shafaroudi (Institue of Medicinal Plants, ACECR, 2022)
Background: Datura innoxia Mill. is one of the medicinal plant which can produce tropan alkaloids such as hyoscyamine and scopolamine with analgesic and antiasthmatic activities. Objective: In this research, the effect of various factors such as culture media and bacteria strain were studied on hairy roots induction and secondary metabolites production in Datura innoxia. Methods: Strains A4, A13, R1000, MSU, 15834, 2656 and 11325 of Agrobacterium rhizogenes with two different concentrations (OD = 0.5, 1) used for co-cultivation of leaf and stem explants prepared from 1-3-month-old and 5-7-month-old plants to optimize the production of hairy roots and then 6 different media were used for establishment and growth of hairy roots. Results: The results of data analysis showed that A4 strain with 86.6 % hairy root production was the best strain than others. Also, dark conditions, younger explants and higher concentration of bacteria caused the highest amount of induction of hairy roots. ½ MS medium was recognized as the best medium for the growth of hairy roots. The results of HPLC analysis also showed that the level of hyoscyamine in hairy roots was lower than that of normal roots which, of course, can be compensated by the higher growth of hairy roots.  Conclusion: The appearance and growth of hairy roots depends on various factors such as bacterial strain, culture medium, explant and its age and other factors that need to be optimized at the beginning of any research.